EFEKTIVITAS KOTAK MISTERI CERITA UNTUK PENGUATAN LITERASI SISWA KELAS 3 SDN 47 AMPENAN - Husna Ma’rufa Rahman; Elya Sulistia Safitri; Fitrianingsih; Linda Sari; M Adi Ilham; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low literacy skills of elementary school students, particularly in reading comprehension and retelling texts, which are influenced by less varied, teacher-centered instructional methods. The study aims to examine the effectiveness of the “Mystery Story Box” as a learning medium to improve the literacy skills of third-grade students at SDN 47 Ampenan. This research employs a qualitative approach using Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, tests, interviews, and documentation, and analyzed using both qualitative descriptive and quantitative methods, with a success indicator of at least 75% of students achieving mastery. The results show that the use of the “Mystery Story Box” significantly improves students’ reading comprehension, retelling skills, and active participation in learning. Therefore, this medium is considered effective as an interactive, engaging, and meaningful innovation in literacy learning for elementary school students.